2012
DOI: 10.1007/s11920-012-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

Components of Emotion Dysregulation in Borderline Personality Disorder: A Review

Abstract: Following Linehan’s biosocial model, we conceptualize emotion dysregulation in borderline personality disorder (BPD) as consisting of four components: emotion sensitivity, heightened and labile negative affect, a deficit of appropriate regulation strategies, and a surplus of maladaptive regulation strategies. We review the evidence supporting each of these components. Given the complexity of the construct of emotion dysregulation and its involvement in many disorders, there is a need for research that specifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
305
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 344 publications
(335 citation statements)
references
References 81 publications
(93 reference statements)
21
305
0
9
Order By: Relevance
“…One explanation for current findings may be found in the type and quality of emotion regulation skills. Indeed, affective instability has previously been interpreted as reflecting a dysfunctional regulation of emotions [8,47]. Although this view mostly stems from the literature on psychopathology, similar processes may play a role when for chronic pain patients have to cope coping with the daily demands of pain [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One explanation for current findings may be found in the type and quality of emotion regulation skills. Indeed, affective instability has previously been interpreted as reflecting a dysfunctional regulation of emotions [8,47]. Although this view mostly stems from the literature on psychopathology, similar processes may play a role when for chronic pain patients have to cope coping with the daily demands of pain [17].…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of affective instability as a reflection of dysfunctional emotion regulation [8,47], we also investigated the relationship between affective instability and measures of emotional functioning,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotion sensitivity refers to the threshold at which a person is able to detect emotional stimuli, while emotion recognition refers to the ability to accurately identify the emotion of detected emotional stimuli [94,95]. As some of the aforementioned studies on ToM have suggested [49], emotion sensitivity and recognition are often studied as a part of, or in tandem with, studies of ToM.…”
Section: Emotion Sensitivity and Recognition In Bpdmentioning
confidence: 99%